(untitled) (Research, Society and Development, 2020)
The learning disability that strikes several children and adolescents, known as dyslexia, is a disorder that affects the ability to read, write, and understand basic concepts for the child’s development during their school life. The recognition and early intervention of the problem are extremely crucial to minimize the negative effects of such disorder, such as the children’s inability to comprehend the classes and teacher’s and parents’ frustration due to low performance and school failure. For this reason, it is necessary to have a greater comprehension of the subject of dyslexia, to develop works related to the disability of this student. From this perspective, this article aims at addressing some concepts and characteristics, and means of intervention related to dyslexia.